Media Bias in China - Qin, Bei; Strömberg, David; Wu, Yanhui (American Economic Review, 2018)
This paper examines whether and how market competition affected the political bias of government-owned newspapers in China from 1981 to 2011. We measure media bias based on coverage of government mouthpiece content ( propaganda) relative to commercial content. We first find that a reform that forced newspaper exits (reduced competition) affected media bias by increasing product specialization, with some papers focusing on propaganda and others on commercial content. Second, lower-level governments produce less-biased content and launch commercial newspapers earlier, eroding higher-level governments’ political goals. Third, bottom-up competition intensifies the politico-economic trade-off, leading to product proliferation and less audience exposure to propaganda. (JEL D72, L31, L82, O14, O17, P26, P31)